An in vivo study of isotropic and anisotropic wall stress in a hyperelastic holzapfel-gasser-ogden model in the human abdominal aorta: Effects of age and sex - Karlsson, Jerker; Stålhand, Jonas; Carlhäll, Carl-Johan; Länne, Toste; Engvall, Jan (Frontiers in Physiology, 2023)
Background: Wall stress of the abdominal aorta (AA) appears to be an important factor in the assessment of risk for rupture based on the relationship between blood pressure and aortic diameter. We therefore investigated peak wall stress as well as isotropic and anisotropic wall stress of AA. Results: Thirty healthy adult males and females were included. Pulsatile diameter changes were determined noninvasively by an echo-tracking system, and intra-aortic pressure was measured simultaneously. A computer based mechanical model was used to compute the isotropic and anisotropic components of circumferential and longitudinal stresses. Elderly males had higher total wall stress and a higher isotropic stress component in circumferential direction and higher total longitudinal wall stress than elderly females. The isotropic component increased with age in males but not in females, whereas the anisotropic component decreased with age in both sexes. Conclusion: We found that isotropic and anisotropic properties of the abdominal aortic wall differ between the young and the elderly participants and between the sexes. A possible explanation could be related to chemical alterations (e.g. due to sex hormones) and changes in the physical distribution of fibers over time. Modeling of wall stress components of the human AA may contribute to a better understanding of elastin-collagen interactions during remodeling of the aortic wall.